Effect of the crystal structure of a deuterated target on the yield of neutrons in the dd reaction at ultralow energies; JETP Letters; Vol. 99, iss. 9 - Bystritsky V. M.; Bystritskii Vit. M.; Dudkin G. N. Gennadiy Nikolaevich; Filipowicz M.; Gazi S.; Huran J.; Mesyats G. A. Gennady Andreyevich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Parzhitskii S. S.; Pen’kov F. M.; Philippov A. V.; et al. (2014, 2014)
Title screen